Advances towards the design and development of personalized non-small-cell lung cancer drug therapy. (November 2013) - Vari, Sabrina; Pilotto, Sara; Maugeri-Saccà, Marcello; Ciuffreda, Ludovica; Cesta Incani, Ursula; Falcone, Italia; Del Curatolo, Anais; Ceribelli, Anna; Gelibter, Alain; De Maria, Ruggero; Tortora, Giampaolo; Cognetti, Francesco; et al.
<x xml:space="preserve">Abstract</x> Introduction: Non-small-cell lung cancer (NSCLC) subtypes are driven by specific genetic aberrations. For reasons such as this, there is a call for treatment personalization. The ability to instigate NSCLC fragmentation poses new methodological problems, and new 'driver' molecular aberrations are being discovered at an unprecedented pace. Areas covered: This article describes the clinical development of epidermal growth factor-tyrosine kinase inhibitors (EGFR-TKIs) and crizotinib for EGFR-mutant and anaplastic lymphoma kinase (ALK)-rearranged NSCLC. Further, the authors briefly describe the emerging molecular targets in NSCLC, in terms of both rationale for therapeutic targeting and strategies, for clinical development. Expert opinion: Target identification and validation in NSCLC still requires considerable effort, as not all of the molecular alterations are clear 'drivers' nor can they be efficiently targeted with available drugs. However, 50% of the NSCLC cases are without clear-defined molecular aberrations. Clinical trial methodology will need to develop novel paradigms for targeted drug development, aiming at the validation of an ideal 'biology-to-trial' approach. Despite significant challenges, a truly 'personalized' approach to NSCLC therapy appears to be within our reach.